Monomeric IgA Antagonizes IgG-Mediated Enhancement of DENV Infection - Wegman, Adam D.; Fang, Hengsheng; Rothman, Alan L.; Thomas, Stephen J.; Endy, Timothy P.; McCracken, Michael K.; Currier, Jeffrey R.; Friberg, Heather; Gromowski, Gregory D.; Waickman, Adam T. (Frontiers in Immunology, 2021)
Dengue virus (DENV) is a prevalent human pathogen, infecting approximately 400 million individuals per year and causing symptomatic disease in approximately 100 million. A distinct feature of dengue is the increased risk for severe disease in some individuals with preexisting DENV-specific immunity. One proposed mechanism for this phenomenon is antibody-dependent enhancement (ADE), in which poorly-neutralizing IgG antibodies from a prior infection opsonize DENV to increase infection of Fc gamma receptor-bearing cells. While IgM and IgG are the most commonly studied DENV-reactive antibody isotypes, our group and others have described the induction of DENV-specific serum IgA responses during dengue. We hypothesized that monomeric IgA would be able to neutralize DENV without the possibility of ADE. To test this, we synthesized IgG and IgA versions of two different DENV-reactive monoclonal antibodies. We demonstrate that isotype-switching does not affect the antigen binding and neutralization properties of the two mAbs. We show that DENV-reactive IgG, but not IgA, mediates ADE in Fc gamma receptor-positive K562 cells. Furthermore, we show that IgA potently antagonizes the ADE activity of IgG. These results suggest that levels of DENV-reactive IgA induced by DENV infection might regulate the overall IgG mediated ADE activity of DENV-immune plasma in vivo, and may serve as a predictor of disease risk.